Electro-thermo-convection in dielectric liquid subjected to partial unipolar injection between two eccentric cylinders. Issue 1 (22nd November 2018) - Elkhazen, Mohamed Issam; Hassen, Walid; Öztop, Hakan F.; Kolsi, Lioua; Al-Rashed, Abdullah A.A.A.; Borjini, Mohamed Naceur; Ali, Mohamed E.
Abstract : Purpose: The purpose of this work is to highlight the effects of partial unipolar injection on electro-thermo-convection (ETC) in dielectric liquid contained between two eccentric cylinders. Design/methodology/approach: A finite volume method was used to solve governing equations. The study is performed for different parameters, such as radius ratio (0.2 ≤ Γ ≤ 0.6), dimensionless electric Rayleigh number (0 ≤ T ≤ 900), eccentricity (−0.4 ≤ e ≤ 0.4) and thermal Rayleigh number (10 ≤ Ra ≤ 5.105). Findings: It is found that heat transfer increases with increase in dimensionless electric Rayleigh number and eccentricity ratio. Originality/value: The originality of this work is to analyze the ETC in dielectric liquid subjected to partial unipolar injection between two eccentric cylinders